On a poorly known Amazonian ant-plant association: Myrcia madida McVaugh (Myrtaceae) and Myrcidris epicharis Ward (Hymenoptera: Formicidae: Pseudomyrmecinae) - Ferreira, Leandro Valle; Vasconcelos, Heraldo Luis de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2010)
Ecological data are provided for the first time on the myrmecophilious relationship between the ant Myrcidris epicharis Ward (Hymenoptera: Formicidae: Pseudomyrmecinae) and the Amazonian tree Myrcia madida McVaugh (Myrtaceae), the only Neotropical species of its family to produce domatia in hollow branches. Ants were collected from 30 plants of various sizes (0.9 to 18 m in height) and all plants were inhabited by Myrcidris epicharis Ward. On average, there were 13.3 adult ant workers, 3.8 larvae, 1.5 pupae, and 2.3 eggs per domatium. Ants tend scale insects that live inside the hollow stems. New colonies of M. epicharis are founded by a single queen, and in none of the plants examined more than one queen was found, suggesting that secondary adoption of queens may not take place in this ant species. Myrcidris epicharis Ward appears to provide protection to its host-plant against both vertebrate and invertebrate herbivores.